2015
DOI: 10.1016/j.jns.2015.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Serial measurements of phosphorylated neurofilament-heavy in the serum of subjects with amyotrophic lateral sclerosis

Abstract: There is a need for a blood biomarker of disease activity in ALS. This marker needs to measure the loss of motor neurones. Phosphorylated neurofilament heavy chain (pNfH) in the serum is a biomarker of axonal injury. Previous studies have found that levels of pNfH are elevated in ALS. We have performed a serial study of pNfH levels in 98 subjects from our ALS clinic. There was significant elevation of levels of pNfH in subjects with ALS compared to controls, although there was considerable variability. In stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
4
56
0
2
Order By: Relevance
“…Recent longitudinal studies examining pNFH in CSF or blood show relatively stable levels over time, though levels of pNFH in serum appeared to increase at early stages of the disease [34,43]. Weydt et al measured levels of pNFH and NFL in CSF and blood of symptomatic and asymptomatic carriers of disease causing mutations to determine if either biomarker could be detected in symptomatic individuals [44].…”
Section: Neurofilament Proteinsmentioning
confidence: 99%
“…Recent longitudinal studies examining pNFH in CSF or blood show relatively stable levels over time, though levels of pNFH in serum appeared to increase at early stages of the disease [34,43]. Weydt et al measured levels of pNFH and NFL in CSF and blood of symptomatic and asymptomatic carriers of disease causing mutations to determine if either biomarker could be detected in symptomatic individuals [44].…”
Section: Neurofilament Proteinsmentioning
confidence: 99%
“…There was no significant difference in levels of NFH between patients treated with Riluzole and those without [173] . Bulbar onset patients were reported to have elevated concentration of NFH in plasma compared with spinal onset patients [175] .…”
Section: Figure 5 Nfh Blood Als-healthymentioning
confidence: 70%
“…There is significant difference between the two groups (P< 0.0001) Symptomatic ALS gene mutation carriers had significantly increased blood levels of NFL compared to asymptomatic carriers of causative mutations [167] . There were no differences in the blood NFL level between ALS patients treated with Riluzole and those without [173] . Three papers found that there was a high correlation of NFL levels between CSF and serum and/or plasma [167,178,179] .…”
Section: Nfl Levels In Blood 3351 Als Versus Healthy Controls/contmentioning
confidence: 73%
See 2 more Smart Citations